مقاصد الصوم الاجتماعية من منظور القرآن الكريم والسنة النبوية: دراسة تحليلية = Social objectives of fasting from the perspective of the Qur'an and the sunnah: an analytical study - Danishfar, Abdul Fatah; Elatrash, Radwan Jamal Yousef (Al-Hikmah Research and Publication Centre, 2024)
تتناول هذه المقالة المقاصد الاجتماعية للصوم من خلال منظور القرآن الكريم، مستعرضةً الأبعاد العميقة التي يُضفيها الصوم على الحياة الاجتماعية للمؤمنين، كما يستند المقال إلى بعض النصوص القرآنية وبعض الأحاديث النبوية الصحيحة لتوضيح كيف يساهم الصوم في تعزيز القيم الاجتماعية والإنسانية. ذلك أن أهم مقاصد الصوم الاجتماعية تعزيز الإحساس والدعم والتعاطف مع فئة الضعفاء من المؤمنين الفقراء والمحتاجين، ناهيك عن أنه يساهم في تجديد التربية الاجتماعية والقيم الأخلاقية، مثل الصبر والتحكم في النفس وتحفيز الأعمال الخيرية والإفطار الجماعي والصلاة المشتركة التي تعين على فهم الروابط الاجتماعية واستكشاف فوائد الصوم الاجتماعية، ويستخدم هذا البحث المنهج الاستقرائي، من خلال تتبع النصوص ذات الصلة بالموضوع. كما أن البحث يعتمد على المنهج التحليلي، وذلك لمناقشة الأفكار التي استنبطت من النصوص والتي تم دراستها لتعين على استنباط مقاصد اجتماعية للصوم من خلال الآيات الكريمة التي تحدث عن الصوم. وقد توصل البحث إلى نتائج مهمة، منها: أن الصوم له مقاصد اجتماعية .عظيمة، يسعى المقال إلى إبراز جزء منها، على اعتبار أن الصوم ليس عبادة فردية فقط، بل هو أداة فعالة لتعزيز التماسك الاجتماعي وتحقيق العدالة بين أفراد المجتمع. This article explores the social purposes of fasting from the perspective of the Quran examining the profound impacts fasting has on the social life of believers. The article relies on Quranic texts to illustrate how fasting contributes to the enhancement of social and humanitarian values. Among the primary social objectives of fasting are fostering a sense of empathy ،support ،and compassion towards the vulnerable ،including the poor and needy among believers. Additionally ،fasting plays a role in renewing social education and ethical values ، such as patience ،self-control ،and encouraging charitable activities ،communal iftar ،and joint prayers ،which help in understanding social connections and exploring the social benefits of fasting. The research employs an inductive approach by tracing relevant texts on the subject ،as well as an analytical method to discuss the ideas derived from these texts and to deduce social objectives of fasting through the Quranic verses about fasting. The study has reached significant conclusions ،including the notion that fasting has profound social purposes ،with the article aiming to highlight some of these ،considering fasting not only as an individual act of worship but also as an effective tool for promoting social cohesion and achieving justice among community members.